Раскрываем скобки: 27a3 - 9a2 + 3a + 9a2 - 3a + 1
Приводим подобные слагаемые:
27a3 + (- 9a2 + 9a2) + (3a - 3a) + 1 = 27a3 + 0 + 0 + 1 = 27a3 + 1
Подставляем в упрощенное выражение значение a = - 1,3
27 х (- 1,3)3 + 1 = 27 х (- 1,27) + 1 = 1,1 х (- 1,1) + 1 = - 1 + 1 = 0.
Раскрываем скобки: 27a3 - 9a2 + 3a + 9a2 - 3a + 1
Приводим подобные слагаемые:
27a3 + (- 9a2 + 9a2) + (3a - 3a) + 1 = 27a3 + 0 + 0 + 1 = 27a3 + 1
Подставляем в упрощенное выражение значение a = - 1,3
27 х (- 1,3)3 + 1 = 27 х (- 1,27) + 1 = 1,1 х (- 1,1) + 1 = - 1 + 1 = 0.